The relationship between preschool teachers' knowledge and attitudes/beliefs - Kong, Esther Sing Yii (2024)
Sexual learning (SL) is not widely implemented in the context of Malaysia preschools. This research paper attempted to study the relationship between preschool teachers’ knowledge and attitudes/beliefs towards SL for preschool children in Malaysia. It was hoped to raise awareness among preschool teachers towards the importance of implementing SL and address the knowledge gap about SL from teachers’ perspectives. Albert Bandura’s self-efficacy theory was applied to the study. It was proposed that the knowledge and attitudes/beliefs would each contribute to the teachers’ self-efficacy and lastly impacted the action they take upon sexual learning. Quantitative research method and correlational design was applied. 90 Malaysian preschool teachers were recruited through convenience sampling method to answer the ‘Questionnaire on Young Children’s Sexual Learning’. The finding indicates there is a significant moderate, positive correlation between level of knowledge and attitudes/beliefs among preschool teachers towards young children’s SL (rs=.438, p<.001). This result showed that as knowledge increases, attitudes/beliefs increase and vice versa. Descriptive analysis revealed that Malaysian preschool teachers exhibit a low level in knowledge (M=4.38, SD=3.51) and a neutral to slightly positive attitudes/beliefs (M=89.30, SD=10.30) regarding SL for preschool children. Inferential analysis revealed that as knowledge increases, attitudes increase and vice versa. These two variables have considerable influence upon each other.Teachers’ level of knowledge and attitudes/beliefs can be improved by providing SL-related trainings and suitable resources as well as support. As recommendations, qualitative or mixed method approach is preferred over quantitative method to gain a deeper insight into teachers’ perspective. Next, random sampling size is suggested for obtaining a large sample size efficiently to increase the reliability of the results.